Research of physical and chemical indices and rheological properties of apple puree different sorts and processing methods - Григоренко, Олена Віталіївна; Григоренко, Елена Витальевна; Нryhorenko, Olena; Вершков, Олександр Олександрович; Вершков, Александр Александрович; Vershkov, Оleksandr (УВ МААО, 2014)
EN: The results of physical and chemical indices research of different apple sorts as well as organoleptic and rheological properties of the apple puree preserved by different methods have been considered. The selection of the best quality sorts and processing methods for the purpose of improvement in the quality of apple puree has been substantiated. UK: В роботі наведено результати досліджень фізико-хімічних показників яблук різних сортів та органолептичні і реологічні властивості виготовленого з них пюре, яке консервоване різними методами. Обґрунтовано вибір кращих сортів та методів обробки з метою підвищення якості яблучного пюре.
Дослідження фізико-хімічних показників та реологічних властивостей яблучного пюре різних сортів та методів обробки
Keywords: apples; apple puree quality; chemical indices; physical indices; processing methods; apparent viscosity; яблука; якість пюре; фізико-хімічні показники; методи обробки; ефективна в’язкість